Periosteum tissue engineering in an orthotopic in vivo platform. (March 2017) - Baldwin, J.G.; Wagner, F.; Martine, L.C.; Holzapfel, B.M.; Theodoropoulos, C.; Bas, O.; Savi, F.M.; Werner, C.; De-Juan-Pardo, E.M.; Hutmacher, D.W.
Abstract: The periosteum plays a critical role in bone homeostasis and regeneration. It contains a vascular component that provides vital blood supply to the cortical bone and an osteogenic niche that acts as a source of bone-forming cells. Periosteal grafts have shown promise in the regeneration of critical size defects, however their limited availability restricts their widespread clinical application. Only a small number of tissue-engineered periosteum constructs (TEPCs) have been reported in the literature. A current challenge in the development of appropriate TEPCs is a lack of pre-clinical models in which they can reliably be evaluated. In this study, we present a novel periosteum tissue engineering concept utilizing a multiphasic scaffold design in combination with different human cell types for periosteal regeneration in an orthotopic in vivo platform. Human endothelial and bone marrow mesenchymal stem cells (BM-MSCs) were used to mirror both the vascular and osteogenic niche respectively. Immunohistochemistry showed that the BM-MSCs maintained their undifferentiated phenotype. The human endothelial cells developed into mature vessels and connected to host vasculature. The addition of an in vitro engineered endothelial network increased vascularization in comparison to cell-free constructs. Altogether, the results showed that the human TEPC (hTEPC) successfully recapitulated the osteogenic and vascular niche of native periosteum, and that the presented orthotopic xenograft model provides a suitable in vivo environment for evaluating scaffold-based tissue engineering concepts exploiting human cells. Graphical abstract: Highlights: Human BM-MSCs transplanted within a star-PEG Heparin hydrogel carrier retained their undifferentiated phenotype in vivo. Human endothelial cells developed into mature functional vessels and connected to host vasculature. The orthotopic xenograft model provides a suitable platform to study human tissue engineered periosteal constructs.